The effects of male age on sperm analysis by motile sperm organelle morphology examination (MSOME) - Silva, Liliane F. I. [UNESP]; Oliveira, Joao Batista A. [UNESP]; Petersen, Claudia G. [UNESP]; Mauri, Ana L.; Massaro, Fabiana C.; Cavagna, Mario; Baruffi, Ricardo L. R.; Franco, Jose G. [UNESP] (Biomed Central Ltd., 2012)
Background: This study aimed to investigate the influence of age on sperm quality, as analysed by motile sperm organelle morphology examination (MSOME).Methods: Semen samples were collected from 975 men undergoing evaluation or treatment for infertility. Sperm cells were evaluated at 8400x magnification using an inverted microscope equipped with Nomarski (differential interference contrast) optics. Two forms of spermatozoa were considered: normal spermatozoa and spermatozoa with large nuclear vacuoles (LNV, defined as vacuoles occupying > 50% of the sperm nuclear area). At least 200 spermatozoa per sample were evaluated, and the percentages of normal and LNV spermatozoa were determined. The subjects were divided into three groups according to age: Group I, less than or equal to 35 years; Group II, 36-40 years; and Group III, greater than or equal to 41 years.Results: There was no difference in the percentages of normal sperm between the two younger (I and II) groups (P > 0.05). The percentage of normal sperm in the older group (III) was significantly lower than that in the younger (I and II) groups (P < 0.05). There was no difference in the percentage of LNV spermatozoa between the younger (I and II) groups (P > 0.05). The percentage of LNV spermatozoa was significantly higher in the older group (III) than in the younger (I and II) groups (P < 0.05). Regression analysis demonstrated a significant decrease in the incidence of normal sperm with increasing age (P < 0.05; r = -0.10). However, there was a significant positive correlation between the percentage of spermatozoa with LNV and male age (P < 0.05, r = 0.10).Conclusion: The results demonstrated a consistent decline in semen quality, as reflected by morphological evaluation by MSOME, with increased age. Considering the relationship between nuclear vacuoles and DNA damage, these age-related changes predict that increased paternal age should be associated with unsuccessful or abnormal pregnancy as a consequence of fertilisation with damaged spermatozoa. Given that sperm nuclear vacuoles can be evaluated more precisely at high magnification, these results support the routine use of MSOME for ICSI as a criterion for semen analysis.
Keywords: Male age; MSOME; IMSI; Sperm morphology; DNA damage